Assessment of tethered harvester productivity in steep terrain conditions: A case study in Western Oregon, USA (Journal of Forestry, 2025)
The use of winch-assisted (tethered) mechanized harvesting systems has recently increased on steep terrain in the Pacific Northwest, USA. Tethered systems are used to support and stabilize the operation of production machines such as harvesters, feller bunchers, forwarders, and grapple skidders on steep slopes. Studies on the environmental impacts, productivity, and costs of these systems should be in focus due to the rapid use of winch-assisted systems in forestry. In this study, a tethered harvester operation working was evaluated using time and motion study analysis. The study was conducted in a clear-cutting area within a Douglas-fir stand in the Oregon Coast Range near Corvallis, Oregon, United States. The production activities were evaluated in stages, including the tethered harvester moving to the tree, preparing for cutting, cutting, and processing. The most time-consuming work stage in the study was determined to be the processing time of the tree. The average delay-free efficiency of the tethered harvester was determined as 40.16 m3/h, while the minimum efficiency was 16 m3/h and the maximum efficiency was 75.02 m3/h. Production efficiency was mostly affected by tree size, with productivity increasing as tree size increased. Statistical analysis showed that there was a significant relationship between tree height, tree diameter, tree volume, and productivity.